Analisis Peranan Kepuasan Dan Komitmen Sebagai Perantara Pengaruh Kualitas Jasa Tutorial Online Terhadap Loyalitas Mahasiswa - Andy Mulyana; Devi Ayuni (Universitas Multimedia Nusantara, 2017)
This study aims to evaluate the role of satisfaction and commitment as mediating the effect of service quality on student loyalty as the user of Open University's Online Tutorial. Based on data analysis on student of Management program 229 as respondents with Structural Equation Modeling (SEM), this study found the relationship between: (1) positive influence of service quality to satisfaction and loyalty of students using tuton; (2) the positive effect of satisfaction on student loyalty using tuton; (3) satisfaction is a mediator between service quality and loyalty of students using tuton. Conversely, commitment has no positive effect on student loyalty as a tuton user. In addition, commitment does not mediates the effect of satisfaction on the loyalty of tuton users. Keywords: service quality, satisfaction, commitment, loyalty